Overexpression of the Maize ZmNLP6 and ZmNLP8 Can Complement the Arabidopsis Nitrate Regulatory Mutant nlp7 by Restoring Nitrate Signaling and Assimilation - Cao, Huairong; Qi, Shengdong; Sun, Mengwei; Li, Zehui; Yang, Yi; Crawford, Nigel M.; Wang, Yong (Frontiers in Plant Science, 2017)
Nitrate is a key nutrient that affects maize growth and yield, and much has yet to be learned about nitrate regulatory genes and mechanisms in maize. Here, we identified nine ZmNLP genes in maize and analyzed the functions of two ZmNLP members in nitrate signaling. qPCR results revealed a broad pattern of expression for ZmNLP genes in different stages and organs with the highest levels of transcript expression of ZmNLP6 and ZmNLP8. When ZmNLP6 and ZmNLP8 were overexpressed in the Arabidopsis nitrate regulatory gene mutant nlp7-4, nitrate assimilation and induction of nitrate-responsive genes in the transgenic plants were recovered to WT levels, indicating that ZmNLP6 and ZmNLP8 can replace the essential roles of the master nitrate regulatory gene AtNLP7 in nitrate signaling and metabolism. ZmNLP6 and ZmNLP8 are localized in the nucleus and can bind candidate nitrate-responsive cis-elements (NREs) in vitro. The biomass and yield of transgenic Arabidopsis lines overexpressing ZmNLP6 and ZmNLP8 showed significant increase compared with WT and nlp7-4 mutant line in low nitrate conditions. Thus, ZmNLP6 and ZmNLP8 regulate nitrate signaling in transgenic Arabidopsis plants and may be potential candidates for improving nitrogen use efficiency (NUE) of maize.